Upcycling of spent copper wires for photocatalysis and supercapacitor applications - Yudha, Cornelius Satria; Apriliyani, Enni; Arinawati, Meidiana (Penerbit Universiti Kebangsaan Malaysia, 2024)
In this study, copper wires were upcycled as copper oxide (CuO) powder through hydrometallurgical and biotreatment processes, which are economically and environmentally attractive. Lactic acid, an organic weak acid, is chosen as the lixiviant to improve the sustainability of the leaching process; meanwhile, Camellia sinensis leaf extract is chosen for the biogenesis of CuO particles. The leaching behavior was investigated. A crystallized Cu powder was successfully generated during the biogenesis process, which became the precursor to CuO. The sintering of Cu resulted in high crystalline CuO particles with monoclinic structure (space group C2/c) based on several characterization methods such as X-ray diffraction analysis and Fourier transform Infrared spectroscopy. SEM images exhibited the submicron secondary particle with a raspberry-like shape of CuO and nanosized primary particles. The band gap of the as-prepared CuO is 3.17 eV. The as-prepared CuO particles were used as a photocatalyst and an active supercapacitor material. The photocatalytic performance was evaluated in a photodegradation process of acid orange 7 (AO7) and methyl orange (MO) dyes, which are considered harmful to the environment. The AO7 and MO photodegradation efficiency are 92.5 and 97.8, respectively. The electrochemical performance of CuO particles showed a pseudocapacitive behavior with a specific capacitance of 252 and 120 F/g at a current density of 0.5 and 5 A/g in 5 M of KOH electrolyte, respectively. This approach can be applied for numerous applications, specifically in overcoming heavy metal pollution from wide selections of metal-based wastes.